Semiotic of Colour and Lighting in Horror Movie The Conjuring 2013 Building Atmosphere Dread - Sihombing, Justruada; Sinambela, Erika; Pasaribu, Donna Ria (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
This research explores the profound significance of visual semiotics in contemporary horror cinema, where atmospheric construction has become a primary tool for evoking psychological terror. Despite the success of elevated horror, a literature gap remains regarding the granular semiotic analysis of how specific technical elements specifically color and lighting function as a sign system to maintain sustained dread. This study aims to identify the dominant semiotic elements of color and lighting in James Wan’s The Conjuring (2013) and analyze their effects in creating a harrowing atmosphere. Utilizing a qualitative descriptive design with a semiotic approach, the study examines 20 purposively selected scenes through Roland Barthes’ three orders of signification: denotation, connotation, and myth. Key findings reveal that the dominant semiotic markers include a desaturated color palette dominated by dark brown, greenish-grey, and black and low-key lighting techniques such as chiaroscuro and backlighting. Denotatively, these elements signify historical periodization and low visibility; connotatively, they signify spiritual corruption, isolation, and vulnerability. Furthermore, the research identifies that these visual signs coalesce into a cinematic "myth" of the domestic space as a predatory organism. The study concludes that the film’s efficacy in inducing dread is a deliberate semiotic construction; the empirical data shows that 'visual uncertainty' produced by the strategic obscuring of shadows through chiaroscuro and negative space compels the audience to project internal fears into the frame's unlit areas. These findings imply that in atmospheric horror, the manipulation of the viewer's perception through chromatic and luminant signs is more critical for emotional impact than explicit narrative or physical violence.